Direct shoot organogenesis and plant regeneration from hypocotyl explants in selected genotypes of Leucaena leucocephala - a leguminous pulpwood tree - Sirisha, V. L.; Prashant, S.; Ranadheer, D.; Ramprasad, P.; Shaik, N. M.; Arha, Manish; Gupta, S. K.; Srivastava, Sarneer; Yadav, A. K.; Kulkarni, P. S.; Othalathara U. Abhilash; Khan, Bashir Mohammad; et al. (Indian Journal of Biotechnology, 2008)
An efficient in vitro plant regeneration system in subabul (Leucaena leucocephala), a leguminous pulp wood tree species, was established. The induction of shoots was achieved from selected elite clones of subabul K-8, K-636 and also wild type on MS medium supplemented with 2% sucrose and different concentrations (0.88 to 24.6 mu M) of plant growth regulators (BA, Kn, 2iP & TDZ). The best medium for shoot regeneration was MS with 22.2 mu M BA (5 shoots per explant), followed by 22.7 mu M TDZ (4.6 shoots per explant). Addition of putriscine (9.3 mu M) to MS medium containing 22.2 mu M BA enhanced the number of multiple shoots to 7-8 but not the frequency of response. Shoot initials (measuring 1 cm) when separated and transferred on to MS medium containing 1.4 mu M GA(3) elongated to 2-5 cm in 15.20 d with 80% frequency. The per cent frequency of shoot differentiation was almost identical in the genotypes K-8 and K-636 but it differed significantly from the wild type. Leaf yellowing and abscission in all the genotypes was curtailed by supplementing the medium with 685 mu M glutamine or 540 mu M adenine. The excised shoots were transferred to root regeneration media containing 2.46 and 4.98 mu M IBA or 2.6 and 5.3 mu M NAA. Root regeneration was noticed with 100% frequency in all the three genotypes in presence of IBA or NAA. Plantlets were transferred successfully to the pots with 70% survival rate with no visible morphological variations. The protocol can be utilized for mass propagation and genetic transformation studies of this important pulpwood species.
Keywords: hypocotyl explants; Leucaena lucocephala; pulpwood leguminous tree; shoot organogenesis

Isolation and heterologous expression of PHA synthesising genes from Bacillus thuringiensis R1 - Desetty, Rohini D.; Mahajan, Vineet S.; Khan, Bashir Mohammad; Rawal, Shuban K. (World Journal of Microbiology & Biotechnology, 2008)
The polyhydroxyalkanoate biosynthesis gene locus from Bacillus thuringiensis R1 was isolated, cloned and analyzed at the molecular level. We found that a similar to 5 kb SacI-ClaI digested fragment of genomic DNA from B. thuringiensis R1 encoding the PHA synthesising genes, conferred PHA producing ability to E. coli. The fragment was sequenced and found to be of 4787 bp with five open reading frames. Sequence alignment with closely related species of Bacillus in the existing database revealed that the ORFs correspond to phaP, phaQ, phaR, phaB and phaC genes. However, E. coli harboring phaP, phaQ, phaR, phaB and phaC locus produced very low PHA. Furthermore, complementation of the locus with phaA from Ralstonia eutropha increased the PHA production in the recombinant E. coli from 3.0% to 24% of cell dry mass. The putative promoter regions and ribosome binding sites were identified for each of the gene. Conserved domains for PHA synthase and aceto-acetyl-coA reductase were also identified. We hence conclude that the PHA operon of Bacillus thuringiensis R1 consists of phaP, phaQ, phaR, phaB, phaC and complementation of the same with phaA is accountable for its high PHA production.
Keywords: aceto-acetyl-coA reductase; Bacillus thuringiensis R1; PHA synthase; polyhydroxyalkanoate

Characterization of the smallest dimeric bile salt hydrolase from a thermophile brevibacillus sp. - Sridevi, N.; Srivastava, Sameer; Khan, Bashir Mohammad; Prabhune, Asmita Ashutosh (Extremophiles, 2009)
A thermophilic microorganism producing bile salt hydrolase was isolated from hot water springs, Pali, Maharashtra, India. This microorganism was identified as Brevibacillus sp. by 16S rDNA sequencing. Bile salt hydrolase (BSH) was purified to homogeneity from this thermophilic source using Q-sepharose chromatography and its enzymatic properties were characterized. The subunit molecular mass of the purified enzyme was estimated to be 28 kDa by SDS-PAGE and, 28.2 kDa by MALDI-TOF analysis. The native molecular mass was estimated to be 56 kDa by gel filtration chromatography, indicating the protein to be a homodimer. The pH and temperature optimum for the enzyme catalysis were 9.0 and 60A degrees C, respectively. Even though BSH from Brevibacillus sp. hydrolyzed all of the six major human bile salts, the enzyme preferred glycine conjugated substrates with apparent K (M) and k (cat) values of 3.08 mu M and 6.32 x 10(2) s(-1), respectively, for glycodeoxycholic acid. The NH2-terminal sequence of the purified enzyme was determined and it did not show any homology with other bacterial bile salt hydrolases. To our knowledge, this is the first report describing the purification of BSH to homogeneity from a thermophilic source.
Keywords: Bile salt hydrolase; Brevibacillus sp.; Dimeric intracellular enzyme; Purification; Thermophile

Phylogenetic analysis, homology modelling, molecular dynamics and docking studies of caffeoyl-CoA-O- methyl transferase (CCoAOMT 1 and 2) isoforms isolated from subabul (Leucaena leucocephala) - Pagadala, Nataraj Sekhar; Arha, Manish; Reddy, P. S.; Kumar, Ranadheer; Sirisha, V. L.; Prashant, S.; Reddy, K. Janardhan; Khan, Bashir Mohammad; Rawal, S. K.; Kishor, P. B. Kavi (Journal of Molecular Modeling, 2009)
Caffeoyl coenzyme A O-methyltransferase (CCoAOMT) is an important enzyme that participates in lignin biosynthesis especially in the formation of cell wall ferulic esters of plants. It plays a pivotal role in the methylation of the 3-hydroxyl group of caffeoyl CoA. Two cDNA clones that code CCoAOMT were isolated earlier from subabul and in the present study; 3D models of CCoAOMT1 and CCoAOMT2 enzymes were built using the MODELLER7v7 software to find out the substrate binding sites. These two proteins differed only in two amino acids and may have little or no functional redundancy. Refined models of the proteins were obtained after energy minimization and molecular dynamics in a solvated water layer. The models were further assessed by PROCHECK, WHATCHECK, Verify_3D and ERRAT programs and the results indicated that these models are reliable for further active site and docking analysis. The refined models showed that the two proteins have 9 and 10 alpha-helices, 6 and 7 beta-sheets respectively. The models were used for docking the substrates CoA, SAM, SAH, caffeoyl CoA, feruloyl CoA, 5-hydroxy feruloyl CoA and sinapyl CoA which showed that CoA and caffeoyl CoA are binding with high affinity with the enzymes in the presence and absence of SAM. It appears therefore that caffeoyl CoA is the substrate for both the isoenzymes. The results also indicated that CoA and caffeoyl CoA are binding with higher affinity to CCoAOMT2 than CCoAOMT1. Therefore, CCoAOMT2 conformation is thought to be the active form that exists in subabul. Docking studies indicated that conserved active site residues Met58, Thr60, Val63, Glu82, Gly84, Ser90, Asp160, Asp162, Thr169, Asn191 and Arg203 in CCoAOMT1 and CCoAOMT2 enzymes create the positive charge to balance the negatively charged caffeoyl CoA and play an important role in maintaining a functional conformation and are directly involved in donor-substrate binding.
Keywords: Caffeoyl-CoA 3-O-methyl transferase; docking; Modelling; S-adenosyl homocysteine

Nanogold-Loaded sharp-edged carbon bullets as plant-gene carriers - Vijayakumar, Periyasamy S.; Othalathara U. Abhilash; Khan, Bashir Mohammad; Bhagavatula L. V. Prasad (Advanced Functional Materials, 2010)
The higher DNA delivery efficiency into plants by gold nanoparticles embedded in sharp carbonaceous carriers is demonstrated. These nanogold-embedded carbon matrices are prepared by heat treatment of biogenic intracellular gold nanoparticles. The DNA-delivery efficiency is tested on a model plant, Nicotiana tabacum, and is further extended to the monocot, Oryza sativa, and a hard dicot tree species, Leucaena leucocephala. These materials reveal good dispersion of the transport material, producing a greater number of GUS foci per unit area. The added advantages of the composite carrier are the lower plasmid and gold requirements. Plant-cell damage with the carbon-supported particles is very minimal and can be, gauged from the increased plant regeneration and transformation efficiency compared with that of the commercial micrometer-sized gold particles. This is ascribed to the sharp edges that the carbon supports possess, which lead to better piercing capabilities with minimum damage.

Expression analysis of cinnamoyl-CoA reductase (CCR) gene in developing seedlings of Leucaena leucocephala: A pulp yielding tree species - Srivastava, Sameer; Gupta, Ranadheer K.; Arha, Manish; Vishwakarma, Rishi K.; Rawal, Shuban K.; Kishor, P. B. Kavi; Khan, Bashir Mohammad (Plant Physiology and Biochemistry, 2011)
Removal of lignin is a major hurdle for obtaining good quality pulp. Leucaena leucocephala (subabul) is extensively used in paper industry in India; therefore, as a first step to generate transgenic plants with low lignin content, cDNA and genomic clones of CCR gene were isolated and characterized. The cDNA encoding CCR (EC 1.2.1.44) was designated as LI-CCR; the sequence analysis revealed an Open Reading Frame (ORF) of 1005 bp. Phylogenetic analysis showed that LI-CCR sequence is highly homologous to CCRs from other dicot plants. The 2992 bp genomic clone of Leucaena CCR consists of 5 exons and 4 introns. The haploid genome of L leucocephala contains two copies as revealed by DNA blot hybridization. LI-CCR gene was over-expressed in Escherichia coli, which showed a molecular mass of approximately 38 kDa. Protein blot analysis revealed that LI-CCR protein is expressed at higher levels in root and in stem, but undetectable in leaf tissues. Expression of CCR gene in Leucaena increased up to 15 d in case of roots and stem as revealed by QRT-PcR studies in 0-15 d old seedlings. ELISA based studies of extractable CCR protein corroborated with QRT-PCR data. CCR protein was immuno-cytolocalized around xylem tissue. Lignin estimation and expression studies of 5,10 and 15 d old stem and root suggest that CCR expression correlates with quantity of lignin produced, which makes it a good target for antisense down regulation for producing designer species for paper industry. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Cinnamoyl-CoA reductase; Developing seedling; Leucaena leucocephala; Lignin biosynthesis

Silico substrate specificity in bmgt1 and bmgt2 genes of bacopa monniera glycosyltransferases online journal of bioinformatics - Sharma, Ranu; Ruby; Khan, Bashir Mohammad; Suresh, C.G. (Bioinformatics, 2011)

Cloning, characterization and impact of up- and down-regulating subabul cinnamyl alcohol dehydrogenase (CAD) gene on plant growth and lignin profiles in transgenic tobacco - Sirisha, V. L.; Prashant, S.; Kumar, D. Ranadheer; Pramod, S.; Jalaja, N.; Kumari, P. Hima; Rao, P. Maheshwari; Rao, S. Nageswara; Mishra, Preeti; Karumanchi, S. Rao; Khan, Bashir Mohammad; Kishor, P. B. Kavi (Plant Growth Regulation, 2012)
Both cDNA including 5'UTR and 3'UTR and genomic clones of cinnamyl alcohol dehydrogenase (CAD) were isolated and characterized from a pulp-yielding leguminous tree Leucaena leucocephala (LlCAD1). The deduced amino acid sequence shared high identity with orthologous sequences of Acacia mangium x Acacia auriculiformis (83%), Medicago sativa (83%), Nicotiana tabaccum (83%) and Aralia cordata (81%). Full length cDNA contained 78 bases of 5'UTR and 283 bases of 3'UTR, while the genomic clone contained 5 exons and 4 introns. Western blot analysis revealed elevated expression of LlCAD1 in seedling roots and shoots compared to leaves. Sense and antisense CAD tobacco transgenics showed increased and reduced CAD activity accompanied by a change in monomeric lignin composition. Histochemical staining of lignin in down-regulated plants suggested an increase in aldehyde units and a decrease in S/G ratio. Down-regulation of CAD resulted in accumulation of syringic, ferulic, p-coumaric and sinapic acids compared to untransformed controls. These observations were validated by anatomical studies of down-regulated transgenic stems which showed thin walled, elongated phloem and xylem fibres, accompanied by a reduction in the density of vessel elements and amount of secondary xylem when compared to untransformed plants. Furthermore, Klason lignin analysis of CAD antisense transgenics showed 7-32% reduced lignin and normal phenotype as compared to untransformed plants. Such a reduction was not noticed in up-regulated transgenics. These results demonstrate a unique opportunity to explore the significant role that down-regulation of CAD gene plays in reducing lignin content thereby offering potential benefits to the pulp and paper industry.
Keywords: Cinnamyl alcohol dehydrogenase; Lignin down-regulation; Subabul (Leucaena leucocephala); Tobacco

Functional characterization and differential expression studies of squalene synthase from Withania somnifera - Gupta, Neha; Sharma, Poonam; Kumar, R. J. Santosh; Vishwakarma, Rishi K.; Khan, Bashir Mohammad (Molecular Biology Reports, 2012)
Squalene synthase (SQS: EC 2.5.1.21) is a potential branch point regulatory enzyme and represents the first committed step to diverge the carbon flux from the main isoprenoid pathway towards sterol biosynthesis. In the present study, cloning and characterization of Withania somnifera squalene synthase (WsSQS) cDNA was investigated subsequently followed by its heterologous expression and preliminary enzyme activity. Two different types of WsSQS cDNA clones (WsSQS1and WsSQS2) were identified that contained an open reading frames of 1,236 and 1,242 bp encoding polypeptides of 412 and 414 amino acids respectively. Both WsSQS isoforms share 99 % similarity and identity with each other. WsSQS deduced amino acids sequences, when compared with SQS of other plant species, showed maximum similarity and identity with Capsicum annuum followed by Solanum tuberosum and Nicotiana tabacum. To obtain soluble recombinant enzymes, 24 hydrophobic amino acids were deleted from the carboxy terminus and expressed as 6X His-Tag fusion protein in Escherichia coli. Approximately 43 kDa recombinant protein was purified using Ni-NTA affinity chromatography and checked on SDS-PAGE. Preliminary activity of the purified enzymes was determined and the products were analyzed by gas chromatograph-mass spectrometer (GC-MS). Quantitative real-time PCR (qRT-PCR) analysis showed that WsSQS expresses more in young leaves than mature leaves, stem and root.
Keywords: Gas chromatograph-Mass Spectrometer (GC-MS); qRT-PCR; Squalene synthase; Withania somnifera

Biochemical characterization of recombinant cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Vishwakarma, Rishi Kishore; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Recombinant cinnamoyl CoA reductase 1 (Ll-CCRH1) protein from Leucaena leucocephala was overexpressed in Escherichia coli BL21 (DE3) strain and purified to apparent homogeneity. Optimum pH for forward and reverse reaction was found to be 6.5 and 7.8 respectively. The enzyme was most stable around pH 6.5 at 25 degrees C for 90 min. The enzyme showed k(cat)/k(m) for feruloyl, caffeoyl, sinapoyl, coumaroyl CoA, coniferaldehyde and sinapaldehyde as 4.6, 2.4, 2.3, 1.7, 1.9 and 1.2 (x10(6) M-1 s(-1)), respectively, indicating affinity of enzyme for feruloyl CoA over other substrates and preference of reduction reaction over oxidation. Activation energy, E-a for various substrates was found to be in the range of 20-50 kJ/mol. Involvement of probable carboxylate ion, histidine, lysine or tyrosine at the active site of enzyme was predicted by pH activity profile. SAXS studies of protein showed radius 3.04 nm and volume 49.25 nm(3) with oblate ellipsoid shape. Finally, metal ion inhibition studies revealed that Ll-CCRH1 is a metal independent enzyme. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Activation energy; Cinnamoyl CoA esters; Cinnamoyl CoA reductase 1; SAXS; stability

Cinnamate 4-hydroxylase (C4H) genes from leucaena leucocephala: a pulp yielding leguminous tree - Kumar, Santosh; Omer, Sumita; Patel, Krunal; Khan, Bashir Mohammad (Molecular Biology Reports, 2013)
Leucaena leucocephala is a leguminous tree species accounting for one-fourth of raw material supplied to paper and pulp industry in India. Cinnamate 4-Hydroxylase (C4H, EC 1.14.13.11) is the second gene of phenylpropanoid pathway and a member of cytochrome P450 family. There is currently intense interest to alter or modify lignin content of L. leucocephala. Three highly similar C4H alleles of LlC4H1 gene were isolated and characterized. The alleles shared more than 98 % sequence identity at amino acid level to each other. Binding of partial promoter of another C4H gene LlC4H2, to varying amounts of crude nuclear proteins isolated from leaf and stem tissues of L. leucocephala formed two loose and one strong complex, respectively, suggesting that the abundance of proteins that bind with the partial C4H promoter is higher in stem tissue than in leaf tissue. Quantitative Real Time PCR study suggested that among tissues of same age, root tissues had highest level of C4H transcripts. Maximum transcript level was observed in 30 day old root tissue. Among the tissues investigated, C4H activity was highest in 60 day old root tissues. Tissue specific quantitative comparison of lignin from developing seedling stage to 1 year old tree stage indicated that Klason lignin increased in tissues with age.
Keywords: Cinnamate 4-Hydroxylase (C4H); Leucaena leucocephala; lignin; Phenylpropanoid

Functional characterization, homology modeling and docking studies of beta-glucosidase responsible for bioactivation of cyanogenic hydroxynitrile glucosides from Leucaena leucocephala (subabul) - Shaik, Noor M.; Misra, Anurag; Singh, Somesh; Fatangare, Amol B.; Ramakumar, Suryanarayanarao; Rawal, Shuban K.; Khan, Bashir Mohammad (Molecular Biology Reports, 2013)
Glycosyl hydrolase family 1 beta-glucosidases are important enzymes that serve many diverse functions in plants including defense, whereby hydrolyzing the defensive compounds such as hydroxynitrile glucosides. A hydroxynitrile glucoside cleaving beta-glucosidase gene (Llbglu1) was isolated from Leucaena leucocephala, cloned into pET-28a (+) and expressed in E. coli BL21 (DE3) cells. The recombinant enzyme was purified by Ni-NTA affinity chromatography. The optimal temperature and pH for this beta-glucosidase were found to be 45 A degrees C and 4.8, respectively. The purified Llbglu1 enzyme hydrolyzed the synthetic glycosides, pNPGlucoside (pNPGlc) and pNPGalactoside (pNPGal). Also, the enzyme hydrolyzed amygdalin, a hydroxynitrile glycoside and a few of the tested flavonoid and isoflavonoid glucosides. The kinetic parameters K (m) and V (max) were found to be 38.59 mu M and 0.8237 mu M/mg/min for pNPGlc, whereas for pNPGal the values were observed as 1845 mu M and 0.1037 mu M/mg/min. In the present study, a three dimensional (3D) model of the Llbglu1 was built by MODELLER software to find out the substrate binding sites and the quality of the model was examined using the program PROCHEK. Docking studies indicated that conserved active site residues are Glu 199, Glu 413, His 153, Asn 198, Val 270, Asn 340, and Trp 462. Docking of rhodiocyanoside A with the modeled Llbglu1 resulted in a binding with free energy change (Delta G) of -5.52 kcal/mol on which basis rhodiocyanoside A could be considered as a potential substrate.
Keywords: Glycosyl hydrolase family 1; homology modeling; Leucaena leucocephala; Molecular docking

Functional characterization of a flavonoid glycosyltransferase gene from withania somnifera (Ashwagandha) - Singh, Somesh; Vishwakarma, Rishi. K.; Kumar, R. J. Santosh; Sonawane, Prashant D.; Ruby; Khan, Bashir Mohammad (Applied Biochemistry and Biotechnology, 2013)
Glycosylation of flavonoids is mediated by family 1 uridine diphosphate (UDP)-dependent glycosyltransferases (UGTs). Until date, there are few reports on functionally characterized flavonoid glycosyltransferases from Withania somnifera. In this study, we cloned the glycosyltransferase gene from W. somnifera (UGT73A16) showing 85-92 % homology with UGTs from other plants. UGT73A16 was expressed as a His(6)-tagged fusion protein in Escherichia coli. Several compounds, including flavonoids, were screened as potential substrates for UGT73A16. HPLC analysis and hypsochromic shift indicated that UGT73A16 transfers a glucose molecule to several different flavonoids. Based on kinetic parameters, UGT73A16 shows more catalytic efficiency towards naringenin. Here, we explored UGT73A16 of W. somnifera as whole cell catalyst in E. coli. We used flavonoids (genistein, apigenin, kaempferol, naringenin, biochanin A, and daidzein) as substrates for this study. More than 95 % of the glucoside products were released into the medium, facilitating their isolation. Glycosylation of substrates occurred on the 7- and 3-hydroxyl group of the aglycone. UGT73A16 also displayed regiospecific glucosyl transfer activity towards 3-hydroxy flavone compound, which is the backbone of all flavonols and also for a chemically synthesized compound, not found naturally. The present study generates essential knowledge and molecular as well as biochemical tools that allow the verification of UGT73A16 in glycosylation.
Keywords: Flavonoid; glycosylation; Glycosyltransferase; Hypsochromic shift; Plant secondary product glycosyltransferase (PSPG); Withania somnifera

Functional characterization of a glucosyltransferase specific to flavonoid 7-O-glucosides from withania somnifera - Kumar, R. J. Santosh; Ruby; Singh, Somesh; Sonawane, Prashant D.; Vishwakarma, R. K.; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2013)
Flavonoids are a large class of phenylpropanoid-derived secondary metabolites, which are usually glycosylated by UDP-glycosyltransferases with one or more sugar groups. Here, we report the cloning and biochemical characterization of a flavonoid glycosyltransferase gene from Withania somnifera (WsGT), which is an important medicinal plant used in Ayurvedic formulations. Using PCR primers, designed for a highly conserved region of previously reported glycosyltransferases, we were able to isolate the corresponding fragment of the WsGT gene. Rapid amplification of cDNA ends (RACE) was then employed to isolate full-length cDNA, which had an open reading frame of 1,371 bp that encode for 456 amino acids. Phylogenetic analysis indicated that WsGT was similar to that of family 1 GT-B glycosyltransferase. Biochemical analysis revealed that WsGT interacts with UDP-glucose and was capable of regiospecifically glycosylating flavonoid-7-ols, such as apigenin, naringenin, luteolin, diadzein and genistein. Expression profiling studies showed that WsGT was highly expressed in young and mature leaves of W. somnifera. Furthermore, exposure to salicylic acid enhanced the expression of WsGT in the leaves and heat shock treatment resulted in decreased expression of WsGT after an initial increase. This may suggest the role of WsGT in response to abiotic/biotic stresses.
Keywords: Diadzein; Flavonoids; Glycosyltransferase; Withania somnifera

Molecular characterization and differential expression studies of an oxidosqualene cyclase (OSC) gene of Brahmi (Bacopa monniera) - Vishwakarma, Rishi K.; Sonawane, Prashant; Singh, Somesh; Kumari, Uma; Ruby; Khan, Bashir Mohammad (Physiology and Molecular Biology of Plants, 2013)
Triterpenoid saponins are the class of secondary metabolites, synthesized via isoprenoid pathway. Oxidosqualene cyclases (OSCs) catalyzes the cyclization of 2, 3-oxidosqualene to various triterpene skeletons, the first committed step in triterpenoid biosynthesis. A full-length oxidosqualene cyclase cDNA from Bacopa monniera (BmOSC) was isolated and characterized. The open reading frame (ORF) of BmOSC consists of 2,292 bp, encoding 764 amino acid residues with an apparent molecular mass of 87.62 kDa and theoretical pI 6.21. It contained four QxxxxxW motifs, one Asp-Cys-Thr-Ala-Glu (DCTAE) motif which is highly conserved among the triterpene synthases and another MWCYCR motif involved in the formation of triterpenoid skeletons. The deduced amino acid sequence of BmOSC shares 80.5 % & 71.8 % identity and 89.7 % & 83.5 % similarity with Olea europaea mixed amyrin synthase and Panax notoginseng dammarenediol synthase respectively. Phylogenetic analysis revealed that BmOSC is closely related with other plant OSCs. Quantitative real-time PCR (qRT-PCR) data showed that BmOSC is expressed in all tissues examined with higher expression in stem and leaves as compared to roots and floral parts.

Molecular cloning, biochemical characterization, and differential expression of an acetyl-CoA C-acetyltransferase gene (AACT) of brahmi (Bacopa monniera) - Vishwakarma, Rishi K.; Ruby; Singh, Somesh; Sonawane, Prashant D.; Srivastava, Sameer; Kumari, Uma; Kumar, R. J. Santosh; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2013)
Bacopa monniera (Brahmi) is an important Indian medicinal herb found in wet damp and marshy places. It produces medicinally important compounds known as bacosides along with alkaloids like brahmine and herpestine. Bacosides are triterpenoid saponins and their biosynthesis takes place via the isoprenoid pathway starting with acetyl-CoA. Acetyl-CoA C-acetyltransferase (AACT; EC 2.3.1.9), also known as acetoacetyl-CoA thiolase (Thiolase II), catalyzes the condensation of two acetyl-CoA to form 4-C compound acetoacetyl-CoA. Acetoacetyl-CoA is an important starting molecule for biosynthesis of various metabolites. Here, we report the cDNA cloning and characterization of acetyl-CoA C-acetyltransferase gene from B. monniera. The full-length gene was isolated using a RACE PCR protocol. The cDNA encoding AACT was designated as BmAACT (FJ947159) revealed an ORF of 1,218 bp and 405 amino acids, and shares 80 % similarity with other plant AACTs. Phylogenetic analysis showed that BmAACT is related closely to other dicot plants AACTs. The BmAACT gene was over-expressed in Escherichia coli as a 6X His-tag fusion protein and purified to homogeneity by Ni-NTA and gel filtration chromatography. Activity of recombinant protein was confirmed by thiolytic cleavage of acetoacetyl-CoA in the presence of 5 mM Mg2+, showing K (m) and V (max) of 20.67 mu M and 96.21 mu mol/min, respectively, with high catalytic efficiency (k (cat) = 2.30 x 10(5) min(-1)). Quantitative real-time PCR analysis showed that the expression of BmAACT is tissue-specific, and accumulation of transcripts is greater in roots and petals, followed by sepals, stem, leaf and pedicel.
Keywords: Acetyl-CoA C-acetyltransferase; Bacopa monniera; Isoprenoid pathway; Triterpenoid saponin

Over-expression of a subgroup 4 R2R3 type MYB transcription factor gene from Leucaena leucocephala reduces lignin content in transgenic tobacco - Omer, Sumita; Kumar, Santosh; Khan, Bashir Mohammad (Plant Cell Reports, 2013)
LlMYB1 , a subgroup 4 R2R3-type MYB transcription factor gene from Leucaena leucocephala appears to be a repressor of lignin biosynthesis pathway by regulating the transcription of general phenylpropanoid pathway genes. R2R3MYB transcription factors are known to play a wide role in regulating the phenylpropanoid pathway in plants. In this study, we report isolation, cloning and characterization of an R2R3MYB transcription factor gene (LlMYB1) from an economically important tree species, Leucaena leucocephala. LlMYB1 consists of 705 bp coding sequence corresponding to 235 amino acids. Sequence alignment revealed that the N-terminal (MYB) domain of the gene shares up to 95 % similarity with subgroup 4 (Sg4) members of R2R3Myb gene family functionally known to be lignin repressors. Highly divergent C-terminal region of the gene carried an ERF-associated amphiphilic repression (EAR) motif, another characteristic of the Sg4. The gene was phylogenetically grouped closest with AmMYB308, a known repressor of monolignol biosynthetic pathway genes. Spatio-temporal expression studies at different ages of seedlings using quantitative real-time PCR (QRT-PCR) showed highest transcript level of the gene in 10 day old stem tissues. Over-expression of the gene in transgenic tobacco showed statistically significant decline in the transcript levels of the general phenylpropanoid pathway genes and reduction in lignin content. Our study suggests that LlMYB1 might be playing the role of a repressor of lignin biosynthesis in L. leucocephala.
Keywords: Leucaena leucocephala; lignin; R2R3MYB; Repressor; Transcript level

Probing the active site of cinnamoyl CoA reductase 1 (Ll-CCRH1) from Leucaena leucocephala - Sonawane, Prashant; Patel, Krunal; Vishwakarma, Rishi Kishore; Srivastava, Sameer; Singh, Somesh; Gaikwad, Sushama M.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2013)
Lack of three dimensional crystal structure of cinnamoyl CoA reductase (CCR) limits its detailed active site characterization studies. Putative active site residues involved in the substrate/NADPH binding and catalysis for Leucaena leucocephala CCR (Ll-CCRH1; GenBank: DQ986907) were identified by amino acid sequence alignment and homology modeling. Putative active site residues and proximal H215 were subjected for site directed mutagenesis, and mutated enzymes were expressed, purified and assayed to confirm their functional roles. Mutagenesis of S136, Y170 and K174 showed complete loss of activity, indicating their pivotal roles in catalysis. Mutant S212G exhibited the catalytic efficiencies less than 10% of wild type, showing its indirect involvement in substrate binding or catalysis. R51G, D77G, F30V and I31N double mutants showed significant changes in K-m values, specifying their roles in substrate binding. Finally, chemical modification and substrate protection studies corroborated the presence Ser, Tyr, Lys, Arg and carboxylate group at the active site of Ll-CCRH1. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Chemical modification; Cinnamoyl CoA reductase 1; Docking simulations; homology modeling; Site directed mutagenesis; Substrate protection

Biological synthesis of cationic gold nanoparticles and binding of plasmid DNA - Raju, D.; Vishwakarma, Rishi K.; Khan, Bashir Mohammad; Mehta, Urmil J.; Ahmad, Absar (Materials Letters, 2014)
Nanobiotechnology is the development of eco-friendly experimental processes for the synthesis of nanomaterials. The present work focuses on synthesis of cationic gold nanoparticles (C-GNPs) for biological applications, especially in gene and drug delivery studies. A biosynthesis methodology has been developed for the functionalization of gold nanoparticles to cationic nature. The synthesis of C-GNPs was done by using peanut leaf extract in the presence of cysteamine. The formed C-GNPs were characterized by using UV-visible spectroscopy (UV-vis), the particles sizes and shapes were confirmed by a Transmission electron microscope (TEM) and crystallinity of C-GNPs was characterized by diffraction. The binding of plasmid DNA on the C-GNPs was confirmed by agarose gel electrophoresis. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Cationic; Nanoparticles; Plasmid DNA; synthesis; TEM

Conformational transitions of cinnamoyl CoA reductase 1 from leucaena leucocephala - Sonawane, Prashant D.; Khan, Bashir Mohammad; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2014)
Conformational transitions of cinnamoyl CoA reductase, a key regulatory enzyme in lignin biosynthesis, from Leucaena leucocephala (L1-CCRH1) were studied using fluorescence and circular dichroism spectroscopy. The native protein possesses four trp residues exposed on the surface and 66% of helical structure, undergoes rapid structural transitions at and above 45 C and starts forming aggregates at 55 C. LI-CCRH1 was transformed into acid induced (pH 2.0) molten globule like structure, exhibiting altered secondary structure, diminished tertiary structure and exposed hydrophobic residues. The molten globule like structure was examined for the thermal and chemical stability. The altered secondary structure of Ll -CCRH1 at pH 2.0 was stable up to 90 C. Also, in presence of 0.25 M guanidine hydrochloride (GdnHCI), it got transformed into different structure which was stable in the vicinity of 2 M GdnHCI (as compared to drastic loss of native structure in 2 M GdnHC1) as seen in far UV-CD spectra. The structural transition of LI-CCRH1 at pH 2.0 followed another transition after readjusting the pH to 8.0, forming a structure with hardly any similarity to that of native protein. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aggregation Cinnamoyl CoA reductase; Conformation; Molten globule; Thermostability; Unfolding

Leucaena sp recombinant cinnamyl alcohol dehydrogenase: purification and physicochemical characterization - Patel, Parth; Gupta, Neha; Gaikwad, Sushama M.; Agrawal, Dinesh C.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2014)
Cinnamyl alcohol dehydrogenase is a broad substrate specificity enzyme catalyzing the final step in monolignol biosynthesis, leading to lignin formation in plants. Here, we report characterization of a recombinant CAD homologue (LICAD2) isolated from Leucaena leucocephala. LICAD2 is 80 kDa homodimer associated with non-covalent interactions, having substrate preference toward sinapaldehyde with K-cat/K-m of 11.6 x 10(6) (M-1 s(-1)), and a possible involvement of histidine at the active site. The enzyme remains stable up to 40 C, with the deactivation rate constant (K-d*) and half-life (t(1/2)) of 0.002 and 5 h, respectively. LICAD2 showed optimal activity at pH 6.5 and 9 for reduction and oxidation reactions, respectively, and was stable between pH 7 and 9, with the deactivation rate constant (K-d*) and half-life (t(1/2)) of 7.5 x 10(-4) and 15 h, respectively. It is a Zn-metalloenzyme with 4 Zn2+ per dimer, however, was inhibited in presence of externally supplemented Zn2+ ions. The enzyme was resistant to osmolytes, reducing agents and non-ionic detergents. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cinnamyl alcohol dehydrogenase (CAD); Metalloenzyme; Substrate specificity

Molecular cloning and characterization of genistein 4'-O-glucoside specific glycosyltransferase from Bacopa monniera - Ruby; Kumar, R. J. Santosh; Vishwakarma, Rishi K.; Singh, Somesh; Khan, Bashir Mohammad (Molecular Biology Reports, 2014)
Health related benefits of isoflavones such as genistein are well known. Glycosylation of genistein yields different glycosides like genistein 7-O-glycoside (genistin) and genistein 4'-O-glycoside (sophoricoside). This is the first report on isolation, cloning and functional characterization of a glycosyltransferase specific for genistein 4'-O-glucoside from Bacopa monniera, an important Indian medicinal herb. The glycosyltransferase from B. monniera (UGT74W1) showed 49 % identity at amino acid level with the glycosyltransferases from Lycium barbarum. The UGT74W1 sequence contained all the conserved motifs present in plant glycosyltransferases. UGT74W1 was cloned in pET-30b (+) expression vector and transformed into E. coli. The molecular mass of over expressed protein was found to be around 52 kDa. Functional characterization of the enzyme was performed using different substrates. Product analysis was done using LC-MS and HPLC, which confirmed its specificity for genistein 4'-O-glucoside. Immuno-localization studies of the UGT74W1 showed its localization in the vascular bundle. Spatio-temporal expression studies under normal and stressed conditions were also performed. The control B. monniera plant showed maximum expression of UGT74W1 in leaves followed by roots and stem. Salicylic acid treatment causes almost tenfold increase in UGT74W1 expression in roots, while leaves and stem showed decrease in expression. Since salicylic acid is generated at the time of injury or wound caused by pathogens, this increase in UGT74W1 expression under salicylic acid stress might point towards its role in defense mechanism.
Keywords: Bacopa monniera; Expression analysis; Glycosyltransferase; Immuno-localization; Plant secondary product glycosyltransferase motif

Steady state fluorescence studies of wild type recombinant cinnamoyl CoA reductase (Ll-CCRH1) and its active site mutants - Sonawane, Prashant; Vishwakarma, Rishi Kishore; Singh, Somesh; Gaikwad, Sushama M.; Khan, Bashir Mohammad (Journal of Fluorescence, 2014)
Fluorescence quenching and time resolved fluorescence studies of wild type recombinant cinnamoyl CoA reductase (Ll-CCRH1), a multitryptophan protein from Leucaena leucocephala and 10 different active site mutants were carried out to investigate tryptophan environment. The enzyme showed highest affinity for feruloyl CoA (K (a) = 3.72 x 10(5) M-1) over other CoA esters and cinnamaldehydes, as determined by fluorescence spectroscopy. Quenching of the fluorescence by acrylamide for wild type and active site mutants was collisional with almost 100 % of the tryptophan fluorescence accessible under native condition and remained same after denaturation of protein with 6 M GdnHCl. In wild type Ll-CCRH1, the extent of quenching achieved with iodide (f (a) = 1.0) was significantly higher than cesium ions (f (a) = 0.33) suggesting more density of positive charge around surface of trp conformers under native conditions. Denaturation of wild type protein with 6 M GdnHCl led to significant increase in the quenching with cesium (f (a) = 0.54), whereas quenching with iodide ion was decreased (f (a) = 0.78), indicating reorientation of charge density around trp from positive to negative and heterogeneity in trp environment. The Stern-Volmer plots for wild type and mutants Ll-CCRH1 under native and denatured conditions, with cesium ion yielded biphasic quenching profiles. The extent of quenching for cesium and iodide ions under native and denatured conditions observed in active site mutants was significantly different from wild type Ll-CCRH1 under the same conditions. Thus, single substitution type mutations of active site residues showed heterogeneity in tryptophan microenvironment and differential degree of conformation of protein under native or denatured conditions.
Keywords: Active site mutants; Cinnamoyl CoA reductase; fluorescence; Ligand binding; Solute quenching

Abiotic stress induces change in cinnamoyl CoA reductase (CCR) protein abundance and lignin deposition in developing seedlings of Leucaena leucocephala - Srivastava, Sameer; Vishwakarma, Rishi K.; Arafat, Yasir Ali; Gupta, Sushim K.; Khan, Bashir Mohammad (Physiology and Molecular Biology of Plants, 2015)
Aboitic stress such as drought and salinity are class of major threats, which plants undergo through their lifetime. Lignin deposition is one of the responses to such abiotic stresses. The gene encoding Cinnamoyl CoA Reductase (CCR) is a key gene for lignin biosynthesis, which has been shown to be over-expressed under stress conditions. In the present study, developing seedlings of Leucaena leucocephala (Vernacular name: Subabul, White popinac) were treated with 1 % mannitol and 200 mM NaCl to mimic drought and salinity stress conditions, respectively. Enzyme linked immunosorbant assay (ELISA) based expression pattern of CCR protein was monitored coupled with Phlorogucinol/HCl activity staining of lignin in transverse sections of developing L. leucocephala seedlings under stress. Our result suggests a differential lignification pattern in developing root and stem under stress conditions. Increase in lignification was observed in mannitol treated stems and corresponding CCR protein accumulation was also higher than control and salt stress treated samples. On the contrary CCR protein was lower in NaCl treated stems and corresponding lignin deposition was also low. Developing root tissue showed a high level of CCR content and lignin deposition than stem samples under all conditions tested. Overall result suggested that lignin accumulation was not affected much in case of developing root however developing stems were significantly affected under drought and salinity stress condition.

Bacopa monniera recombinant mevalonate diphosphate decarboxylase: biochemical characterization - Shakeel Abbassi; Vishwakarma, Rishi K.; Patel, Parth; Kumari, Uma; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate diphosphate decarboxylase (MDD; EC 4.1.1.33) is an important enzyme in the mevalonic acid pathway catalyzing the Mg2+-ATP dependant decarboxylation of mevalonate 5-diphosphate (MVAPP) to isopentenyl diphosphate (IPP). Bacopa monniera recombinant MDD (BmMDD) protein was overexpressed in Escherichia coli BL21 (DE3) strain and purified to apparent homogeneity. K-m and V-max for MVAPP were 144 mu M and 52 U mg(-1) respectively. The values of turnover (k(cat)) and k(cat)/K-m, for mevalonate 5-diphosphate were determined to be 40 s(-1) and 2.77 x 10(5) M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found to be 30 s(-1) and 2.20 x 10(4) M-1 s(-1), respectively. pH activity profile indicated the involvement of carboxylate ion, lysine and arginine for the activity of enzyme. The apparent activation energy for the BmMDD catalyzed reaction was 12.7 kJ mol(-1). Optimum pH and temperature for the forward reaction was found to be 8.0 and 45 degrees C. The enzyme was most stable at pH 7 at 20 degrees C with the deactivation rate constant (K-d(*)) of 1.69 x 10(-4) and half life (t(1/2)) of 68 h. The cation studies suggested that BmMDD is a cation dependant enzyme and optimum activity was achieved in the presence of Mg2+. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Mevalonate diphosphate decarboxylase; pH activity profile; Phylogenetic analysis; stability

Biochemical characterization of recombinant mevalonate kinase from Bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Sonawane, Prashant; Shakeel Abbassi; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate kinase (MK; ATP: mevalonate 5-phosphotransferase; EC 2.7.1.36) plays a key role in isoprenoid biosynthetic pathway in plants. MK catalyzes the phosphorylation of mevalonate to form mevalonate-5-phosphate. The recombinant BmMK was cloned and over-expressed in E. coli BL21 (DE3), and purified to homogeneity by affinity chromatography followed by gel filtration. Optimum pH and temperature for forward reaction was found to be 7.0 and 30 degrees C, respectively. The enzyme was most stable at pH 8 at 25 degrees C with deactivation rate constant (Kd*) 1.398 x 10(-4) and half life (t(1/2)) 49 h. pH activity profile of BmMK indicates the involvement of carboxylate ion, histidine, lysine, arginine or aspartic acid at the active site of enzyme. Activity of recombinant BmMK was confirmed by phosphorylation of RS-mevalonate in the presence of Mg2+, having K-m and V-max 331.9 mu M and 719.1 pKat mu g(-1), respectively. The values of k(cat) and k(cat)/K-m for RS-mevalonate were determined to be 143.82 s(-1) and 0.43332 M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found 150.9 s(-1) and 1.023 M-1 s(-1). The metal ion studies suggested that BmMK is a metal dependent enzyme and highly active in the presence of MgCl2. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bacopa monniera; Enzyme kinetics; Mevalonate kinase; stability

c Squalene synthase gene from medicinal herb bacopa monniera: molecular characterization, differential expression, comparative modeling, and docking studies - Vishwakarma, Rishi K.; Patel, Krunal; Sonawane, Prashant; Kumari, Uma; Singh, Somesh; Ruby; Shakeel Abbassi; Agrawal, Dinesh C.; Tsay, Hsin-Sheng; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2015)
The widespread pharmaceutically important triterpenoid saponins are synthesized via isoprenoid pathway. The formation of squalene is the key regulatory point in triterpene biosynthesis, catalyzed by squalene synthase (SQS). The present study deals with the detailed characterization of SQS by molecular, biochemical, and computational means from Bacopa monniera, an immensely important medicinal plant rich in triterpenoid saponin, bacosides. A full-length SQS gene was isolated from B. monniera, characterized as B. monniera squalene synthase (BmSQS) (1242 bp) encoding 414 amino acids. Deduced amino acid sequence of BmSQS showed highly conserved consensus aspartate-rich motifs (DXXXD) and catalytic site residues. Phylogenetic analysis showed that BmSQS belongs to dicot group having closest relationship with Salvia miltiorrhiza. Semiquantitative and real-time PCR studies showed that the BmSQS messenger RNA (mRNA) expression level was higher in vegetative parts (roots) as compared to floral parts. Methyl jasmonate induces the BmSQS mRNA expression in all tissues tested, while salicylic acid, cold, and salt induce much higher expression in roots. Homology modeling and docking simulations of BmSQS showed the pivotal roles of Asp77, Asp81, Asp213, Asp217, and Tyr168 in catalysis.
Keywords: Abiotic stress; Bacopa monniera; Comparative modeling and docking; Differential expression; Isoprenoid pathway; Squalene synthase

Efficient shoots regeneration and genetic transformation of bacopa monniera - Kumari, Uma; Vishwakarma, Rishi K.; Gupta, Neha; Ruby; Shirgurkar, M. V.; Khan, Bashir Mohammad (Physiology and Molecular Biology of Plants, 2015)
Bacopa monniera is an important source of metabolites with pharmaceutical value. It has been regarded as a valuable medicinal plant and its entire commercial requirement is met from wild natural population. Recently, metabolic engineering has emerged as an important solution for sustained supply of assured and quality raw material for the production of active principles. Present report describes efficient in vitro multiplication and transformation method for geneticmanipulation of this species. MS medium supplemented with 2 mgl(-1) BA and 0.2 mgl(-1) IAA was found optimum for maximum shoot regeneration (98.33 %) from in vitro leaves with 2-3 longitudinal cuts. Agrobacterium tumefaciens-mediated transformation method was used for generating transgenic B. monniera plants. Putative transformants were confirmed by GUS assay and PCR based confirmation of hptII gene. DNA blot analysis showed single copy insertion of transgene cassette. An average of 87.5 % of the regenerated shoots were found PCR positive for hptII gene and GUS activity was detected in leaves of transgenic shoots at a frequency of 82.5 % The efficient multiple shoots regeneration system described herein may help in mass production of B. monniera plant. Also, the high frequency transformation protocol described here can be used for genetic engineering of B. monniera for enhancement of its pharmaceutically important metabolites.

In silico ligand binding studies of cyanogenic beta-glucosidase, dhurrinase-2 from Sorghum bicolor - Mahajan, Chavi; Patel, Krunal; Khan, Bashir Mohammad; Rawal, Shuban S. (Journal of Molecular Modeling, 2015)
Dhurrinase, a cyanogenic beta-glucosidase from Sorghum bicolor is the key enzyme responsible for the hydrolysis of dhurrin to produce toxic hydrogen cyanide, as a part of plant defence mechanism. Dhurrinase 1 (SbDhr1) and dhurrinase 2 (SbDhr2), two isozymes have been isolated and characterized from S. bicolor. However, there is no information in the literature about the three dimensional (3D) structure of SbDhr2 and molecular interactions involved between the protein and ligand. In this study, the three dimensional structure of SbDhr2 was built based on homology modeling by using the X-ray crystallographic structure of its close homologue SbDhr1 as the template. The generated 3D model was energy minimized and the quality was validated by Ramachndran plot, various bioinformatic tools and their relevant parameters. Stability, folding-unfolding and flexibility of the modeled SbDhr2 was evaluated on the basis of RMSD, radius of gyration (R-g) and RMSF values respectively, obtained through molecular dynamic (MD) simulation. Further, molecular docking was performed with its natural substrate dhurrin, one substrate analogue, three un-natural substrates, and one inhibitor. Analysis of molecular interactions in the SbDhr2-ligand complexes revealed the key amino acid residues responsible to stabilize the ligands within the binding pocket through non-bonded interactions and some of them were found to be conserved (Glu239, Tyr381, Trp426, Glu454, Trp511). Reasonably broader substrate specificity of SbDhr2 was explained through the wider entrance passage observed in comparison to SbDhr1.
Keywords: beta-Glucosidase; Dhurrinase; Molecular docking; Molecular dynamic simulation; Sorghum bicolor

Overexpression of squalene synthase in withania somnifera leads to enhanced withanolide biosynthesis - Patel, Neha; Patel, Parth; Kendurkar, Shuchishweta V.; Thulasiram, Hirekodathakallu V.; Khan, Bashir Mohammad (Plant Cell Tissue and Organ Culture, 2015)
Genetic engineering of secondary metabolic pathways is an emerging area of research for production and improvement of natural products in plant biotechnology. Here, we describe a systematic approach to manipulate a key regulatory step of isoprenoid biosynthetic pathway in Withania somnifera to study its effect on withanolide production. We generated T-0 W. somnifera plants overexpressing squalene synthase (WsSQS) by Agrobacterium tumefaciens mediated transformation, which were analyzed by Gus biochemical assay and PCR of hygromycin phosphotransferase (hptII) and WsSQS. qRT-PCR analyses of various transformed tissues indicated 2-5 fold increase in WsSQS transcripts in both T-0 and T-1 generations. The tissue specific protein expression studies revealed 2-3 fold increase in WsSQS, which was further confirmed by enzyme activity. These observations were corroborated with the 1.5-2 fold increase in total withanolide content of the transformed tissues. However, in leaf tissue, the levels of Withaferin A and Withanolide A increased significantly up to 4-4.5 fold. These findings demonstrate genetic engineering of isoprenoid pathway in W. somnifera resulting in enhanced production of withanolides, and also provide insights into such metabolic pathways for their manipulation to improve the pharmacological content of different medicinally important plants.
Keywords: Agrobacterium tumefaciens; Solanaceae; Squalene synthase; Withania somnifera; Withanolides

Functional and conformational transitions of mevalonate diphosphate decarboxylase from Bacopa monniera - Shakeel, Abbassi; Patel, Krunal; Khan, Bashir Mohammad; Bhosale, Siddharth H.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2016)
Functional and conformational transitions of mevalonate diphosphate decarboxylase (MDD), a key enzyme of mevalonate pathway in isoprenoid biosynthesis, from Bacopa monniera (BmMDD), cloned and overexpressed in Escherichia coli were studied under thermal, chemical and pH-mediated denaturation conditions using fluorescence and Circular dichroism spectroscopy. Native BmMDD is a helix dominant structure with 45% helix and 11% sheets and possesses seven tryptophan residues with two residues exposed on surface, three residues partially exposed and two situated in the interior of the protein. Thermal denaturation of BmMDD causes rapid structural transitions at and above 40 degrees C and transient exposure of hydrophobic residues at 50 degrees C, leading to aggregation of the protein. An acid induced molten globule like structure was observed at pH 4, exhibiting altered but compact secondary structure, distorted tertiary structure and exposed hydrophobic residues. The molten globule displayed different response at higher temperature and similar response to chemical denaturation as compared to the native protein. The surface tryptophans have predominantly positively charged amino acids around them, as indicated by higher K-SV for IC as compared to that for CsCl. The native enzyme displayed two different lifetimes, vi (1.203 +/- 0.036 ns) and tau 2 (3.473 +/- 0.12 ns) indicating two populations of tryptophan. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aggregation; CD spectroscopy; Fluorescence quenching; Mevalonate diphosphate decarboxylase; Unfolding